Artificial Intelligence–Assisted English Language Learning: A Collaborative Model between English Education and Informatics - Rani Santika; Rafi Farizki (Riviera Publishing, 2025)
Artificial intelligence (AI) has become increasingly prominent in English as a Foreign Language (EFL) learning, particularly through the use of AI-powered chatbots to support language practice beyond classroom boundaries. However, prior studies report mixed results, often emphasizing technology adoption or learning outcomes while overlooking learners’ psychological experiences. This study aims to examine AI-assisted EFL learning through a collaborative model integrating perspectives from English education and informatics, with a focus on perceived autonomy, perceived interactivity, learner engagement with AI-powered chatbots, and perceived learning outcomes. A quantitative explanatory research design was employed using a cross-sectional survey of EFL learners with prior experience using AI-powered chatbots. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the proposed research model. The results indicate that perceived autonomy and perceived interactivity have significant positive effects on learners’ engagement with AI-powered chatbots. Learner engagement also shows a significant positive effect on perceived learning outcomes and mediates the relationships between autonomy, interactivity, and learning outcomes. The findings highlight the importance of autonomy-supportive and interactive chatbot design and underscore the value of interdisciplinary collaboration between English education and informatics in fostering meaningful and sustainable AI-assisted EFL learning.